Synthesis and biotransformation of diarylpentadienones - Alabi, Zaccheaus Oluwatayo (2019)
SYNTHESIS AND BIOTRANSFORMATION OF DIARYLPENTADIENONES. Naturally-occuring compounds containing bis-aryl moiety are important components of fine chemicals required by pharmaceutical, agrochemical and flavor industries. These compounds have inspired the synthesis of several of their analogs such as the diarylpentadienones. These synthetic analogs possess equal or better potential compared to their lead compounds. As part of the ongoing efforts in our laboratory to enlarge the diarylpentadienones library, we synthesized some monoarylidenes and diarylpentadienones (compounds 2, 4, 5, 6) and biotransformed them and some others obtained from the previous works in our laboratory (compounds 7, 8 and 9) using Penicillium brasilianum and Saccharomyces cerevisiae to modify them and enlarge their library. In our finding, the resting cells of P. brasilianum reduced monoarylidene 2 to 10 and further oxidized it to 11 in a Baeyer-Villiger-like manner. However, no biotransformation product was detected when diarylpentadinones 4, 5, 7 and 8 were fed into the fungi. Also, baker’s yeast Saccharomyces cerevisiae reduced 9 to 10 and 11 in a regioselective manner. Further investigation into why P. brasilianum was not able to reduce and/or oxidized diarylpentadienones used must be carried out.